If the Current Clique Algorithms are Optimal, So is Valiant's Parser - Abboud, Amir; Backurs, Arturs; Williams, Virginia Vassilevska (2015 IEEE 56th Annual Symposium on Foundations of Computer Science, 2015)
The CFG recognition problem is: given a context-free grammar G and a string w of length n, decide if w can be obtained from G. This is the most basic parsing question and is a core computer science problem. Valiant's parser from 1975 solves the problem in O(nO) time, where ? <; 2:373 is the matrix multiplication exponent. Dozens of parsing algorithms have been proposed over the years, yet Valiant's upper bound remains unbeaten. The best combinatorial algorithms have mildly subcubic O(n3= log3 n) complexity. Lee (JACM'01) provided evidence that fast matrix multiplication is needed for CFG parsing, and that very efficient and practical algorithms might be hard or even impossible to obtain. Lee showed that any algorithm for a more general parsing problem with running time O(|G| n3 -- e) can be converted into a surprising subcubic algorithm for Boolean Matrix Multiplication. Unfortunately, Lee' s hardness result required that the grammar size be |G| = O(n6). Nothing was known for the more relevant case of constant size grammars. In this work, we prove that any improvement on Valiant' s algorithm, even for constant size grammars, either in terms of runtime or by avoiding the inefficiencies of fast matrix multiplication, would imply a breakthrough algorithm for the k-Clique problem: given a graph on n nodes, decide if there are k that form a clique. Besides classifying the complexity of a fundamental problem, our reduction has led us to similar lower bounds for more modern and well-studied cubic time problems for which faster algorithms are highly desirable in practice: RNA Folding, a central problem in computational biology, and Dyck Language Edit Distance, answering an open question of Saha (FOCS'14).